2012
DOI: 10.1007/s10495-012-0759-5
|View full text |Cite
|
Sign up to set email alerts
|

Snake venom toxin from Vipera lebetina turanica sensitizes cancer cells to TRAIL through ROS- and JNK-mediated upregulation of death receptors and downregulation of survival proteins

Abstract: We investigated whether snake venom toxin (SVT) from Vipera lebetina turanica enhances the apoptosis ability of tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) in cancer cells. TRAIL inhibited HCT116 cell growth in a dose-dependent manner; however, this reduction did not occur in TRAIL resistant HT-29, A549 and HepG2 cells with an even higher dose of TRAIL. SVT, but not TRAIL enhanced expression of cell death receptor (DR) in TRAIL resistant cancer cells in a dose-dependent manner. A comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Curcumin sensitizes TRAIL-resistant prostate cancer cells in xenograft model through DR4 and DR5 expression and inhibition of p-p65 (Shankar et al 2008). Previously, we found that the combination of SVT and TRAIL increases DR4 and DR5 expression in TRAIL-resistant colon cancer cells (Park et al 2012b). Therefore, it is possible that SVT can overcome resistance to TRAIL through an inactivation of NF-κB and expression of DR3 and DR5 (Park et al 2012b).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Curcumin sensitizes TRAIL-resistant prostate cancer cells in xenograft model through DR4 and DR5 expression and inhibition of p-p65 (Shankar et al 2008). Previously, we found that the combination of SVT and TRAIL increases DR4 and DR5 expression in TRAIL-resistant colon cancer cells (Park et al 2012b). Therefore, it is possible that SVT can overcome resistance to TRAIL through an inactivation of NF-κB and expression of DR3 and DR5 (Park et al 2012b).…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we found that the combination of SVT and TRAIL increases DR4 and DR5 expression in TRAIL-resistant colon cancer cells (Park et al 2012b). Therefore, it is possible that SVT can overcome resistance to TRAIL through an inactivation of NF-κB and expression of DR3 and DR5 (Park et al 2012b).…”
Section: Discussionmentioning
confidence: 94%
“…125 However, other natural compounds such as SVT (snake venom toxin from vipera lebetina turanica), ursolic acid (a pentacyclin triterpene), capsazepine (the active ingredient of chilli pepper), and tricetin (a flavonoid derivative found in Myrtaceae pollen and Eucalyptus Honey) induce DRs mediated by JNK1/2 activation through production of ROS. [126][127][128][129] DRs can also be upregulated by diverse natural compounds through the activation of p38 signaling cascade. Another natural agent, lupulone, a b-acid largely present in hops (Humulus lupulus l), can significantly enhance the expression of p38, which plays a major role in the activation of p53 and the TRAIL-DR apoptotic pathway in SW620 human colon cancer-derived metastatic cells.…”
Section: Natural Compounds That Can Sensitize Tumor Cells To Trailmentioning
confidence: 99%
“…This increment of MDA could be produced due the arachidonic acid release after PLA 2 catalysis [11]. Moreover, the newly produced arachidonic acid could be oxidized by H 2 O 2 produced by the LAAO catalysis [25].…”
Section: Resultsmentioning
confidence: 99%
“…SVMPs, major components in most Crotalid venoms, have a relevant role in venom-induced local damage. The lethality of this venom is due to the high activity of PLA 2 that hydrolyzes phospholipids and releases arachidonic acid, which, in turn, generates toxic reactive oxygen species (ROS) [10, 11]. This reaction results in lipid peroxidation and leads to cellular damage [12].…”
Section: Introductionmentioning
confidence: 99%